Agency or resale: Effects of a platform-performance investment for frenemy platforms - Li, Zhiyong; Ho, Yi-Chun; Nan, Guofang; Li, Minqiang (Decision Support Systems, 2019)
Competing platforms with hardware and content differentiation may adopt a one-way compatibility strategy, in which one platform owner allows its hardware users to purchase the competitor's content service, whereas the competitor does not. Moreover, the platform owners can choose a resale model or agency model. When a platform owner adopts the agency model, a platform-performance investment may force content providers to incur certain costs to ensure enhanced performance. In this paper, we develop a stylized model to investigate the effects of a platform-performance investment on a business-model decision by examining a platform ecosystem that consists of a unit mass of users, a content provider, and two downstream competing platform owners. We find that, when the unit misfit cost of hardware is much less than that of the content, if the royalty rate is too high (low), the agency (resale) model will be adopted by both platform owners. If the royalty rate is neither too high nor too low, the owners will adopt a different business model. When the unit misfit cost of hardware is weakly less than that of the content, the platform owners' business-model decision is jointly determined by the relative platform-performance investment efficiency and the royalty rate. Moreover, when both platform owners adopt the agency model, the price is not always higher than that when they use the resale model due to the negative effect of the performance investment. Finally, we present the condition under which the content provider would be better off if the provider is granted the right to change the business model by one platform owner. •We study an ecosystem including a content provider, two platform owners, and users.•The frenemy (friends and enemies) relationship between platforms is addressed.•The platform-performance investment has different effects on the content provider and users.•The competing platform owners endogenously adopt the agency or the resale model.•The platform-performance investment plays a critical role on business model decisions.